Activity of the Department of Saving the Sick of the Vilnius Charity Society in the first decades of the 19th century (Marginesy, 2021)
The Vilnius Charitable Society (established in 1807) was the first secular charity in Poland. Apart from the material aid to the poor, it also offered them access to the medical care. Within the society, the 3rd department dedicated to saving ill people was established, which main task was to provide a professional medical advice to the poor, supply them with medicine and introduce them to the preventive healthcare. The members of the department consisted of doctors of medicine, surgeons and apothecaries from Vilnius, the majority of whom were employees and graduates from Imperial University of Vilnius. Among new methods of disease prevention promoted by the members of the department was the vaccine against smallpox invented in Britain by Edward Jenner. The department also tended to pregnant women and those in the postpartum period by establishing the Institute of Motherhood. The members of the department shared their medical knowledge in the “Dzieje Dobroczynności Krajowej i Zagranicznej” (“The History of National and Foreign Charity”) journal, which was published in Vilnius in 1820–1824.